Пристрій для дистанційного вимірювання параметрів поверхонь рефлекторів антен - Михайло, Паламар; Ігор, Зелінський; Мирослава, Яворська (Видавництво Львівської політехніки, 2015)
Запропоновано схему приладу та оптичної системи для дистанційного вимірювання координат поверхні рефлектора за принципом суміщення світлових марок від монохромних джгутів. Наведено формули для обчислення координат точок сканованої поверхні за значеннями параметрів приладу. Подано оцінки точності значень вимірюваних величин. Предложена схема прибора и оптической системы для дистанционного измерения координат поверхности рефлектора путем совмещения световых марок от монохромных пучков. Приведены формулы для вычисления координат точек сканированной поверхности, исходя из значений параметров прибора. Даны оценки точности значений измеряемых величин. The scheme of the device and the optical system for reflector surfacemeasurement is proposed. The device implements a triangulation principle in the determination of distance to a remote point. The optical system forms two coaxial light beams of equal intensity. One beam directed at a right angle to the base. At the initial stage of themeasurements second beamis direct in a manner to provide beams tracks juxtaposition on the beginning of the Cartesian coordinate system tied to the scanned surface. The displacement of the light beams tracks on a surface implemented by means of turning of the base around the point of its fixing, and the basis length changing in a neighborhood of its initial length value. The values of the point coordinates are determined through the base displacement and the angle of the base rotation, provided the juxtaposition of both beams. It should be noted that beamtrack on the surface is observed as a diffraction pattern on the ring diaphragmin the far zone with a clear expressed main peak whose diameter at the working distance (about 2–3 m) is approximately 0.2 mm. Visual observation of beams tracks juxtaposition is conduct by means of photographic system, which contains long-focal objective, a set of filters for laser light selection and digital camera.Monitoring is conduct on the computer screen at 50-foldmagnifications ofmain peaks. It allowed us to make a conclusion aboutmain peaks juxtaposition with accuracy ~ 0.1mm. The formulas to calculate the coordinates of the point on the surface scanned through base rotation angle and base length displacement are given. An analysis of the performance parameters ranges of device depending on the size of the surface scanned ismade. Also the sensitivity coefficients ofmeasured values to device parameters are assessed. It is established that the instrumental errors of the device in the range of angle changing within (–5◦, 5◦) and the range of base displacement changing within (–12 cm, 12 cm) do not exceed fractions of tenths of amillimeter. To light beams displacement vertically there is a possibility in the device to rotate the optical system in the plane perpendicular to the base. A map of the surface deviation fromthe shape is formed with regard to assessments of instrumental errors in a defined range of the device settings change.
Keywords: поверхня рефлектора; дистанційне вимірювання; оптична вимірювальна система; інструментальні похибки; поверхность рефлектора; дистанционные измерения; оптическая измерительная система; инструментальные погрешности; reflector surface; distance measurements; optical measurement system; instrumental errors